A continuous flow diffusion chamber study of sea salt particles acting as cloud nuclei: deliquescence and ice nucleation - Xiangrui Kong; Martin J. Wolf; Michael Roesch; Erik S. Thomson; Thorsten Bartels-Rausch; Peter A. Alpert; Markus Ammann; Nønne L. Prisle; Daniel J. Cziczo (Tellus: Series B, Chemical and Physical Meteorology, 2018)
Phase changes of sea salt particles alter their physical and chemical properties, which is significant for Earth’s chemistry and energy budget. In this study, a continuous flow diffusion chamber is used to investigate deliquescence, homogeneous and heterogeneous ice nucleation between 242 K and 215 K, of four salts: pure NaCl, pure MgCl2, synthetic sea water salt, and salt distilled from sampled sea water. Anhydrous particles, aqueous droplets and ice particles were discriminated using a polarisation-sensitive optical particle counter coupled with a machine learning analysis technique. The measured onset deliquescence relative humidities agree with previous studies, where sea water salts deliquescence at lower humidities than pure NaCl. Deliquesced salt droplets homogenously freeze when the relative humidity reaches a sufficiently high value at temperatures below 233 K. From 224 K and below, deposition nucleation freezing on a fraction of NaCl particles was observed at humidities lower than the deliquescence relative humidity. At these low temperatures, otherwise unactivated salt particles deliquesced at the expected deliquescence point, followed by homogeneous freezing at temperatures as low as 215 K. Thus, the observed sea salt particles exhibit a triad of temperature-dependent behaviours. First, they act as cloud condensation particles (CCNs) > 233 K, second they can be homogeneous freezing nuclei (HFNs) < 233 K and finally they act as ice nucleating particles (INPs) for heterogeneous nucleation <224 K.